FORMING CHARACTERS OF EARLY CHILDREN IN NON-FORMAL EDUCATION UNITS - Sopyan Alif; Ahmad Irwan; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2019)
Early Childhood Education which is a form of non-formal education by emphasizing the laying of the foundation towards physical growth and development (fine and gross motor coordination), intelligence (thinking power, creativity, emotional intelligence, spiritual intelligence), socio emotional ( attitudes and behavior as well as religion), language, and communication, in accordance with the uniqueness and stages of development that are passed by early childhood. Therefore, Early Childhood Education plays an important role in children's education. Through Early Childhood Education, children can be educated by their teachers with clear methods and curriculum. They can play and channel their energy through various physical activities, music, or hand skills. Can learn to interact interpersonal and intrapersonal. They can gradually be introduced to letters or reading, the environment, agriculture and even industry. The introduction is not excessive, because the delivery is adapted to the world of children, namely the world of play so that the learning process is fun. Children often express their ideas and feelings through play, so that when they feel enjoy and happy with what is taught, it will automatically benefit their development.